PMO-161 Hepatitis E (HEV) in South West England. Geographical, environmental and social factors: a case control study. (28th May 2012) - Hunter, J; Madden, R; Stone, A; Osborne, N; Wheeler, B; Barlow, M; Bendall, R; Lin, N; Henley, W; Gaze, W; Dalton, H
Abstract : Introduction: HEV is an emerging infection in developed countries, and is considered a porcine zoonosis. HEV has been found in pigs world wide and a number of water courses. In most cases the route of infection remains uncertain. A previous UK study showed that HEV was associated geographically to pig farms and coastal areas. 1 AIM: To study the geographical, environmental and social factors in HEV infection. Methods: Cases of HEV and controls were identified from 2147 consecutive patients attending the Jaundice Hotline clinic, Cornwall (1999–2011). For each case and control the following were recorded: home postcode, distance from home to nearest pig farm, distance from home to coast, rainfall levels during the 8 weeks prior to presentation and socioeconomic status. A further 611 Cornish residents were tested for anti-HEV IgG to determine geographic differences in HEV seroprevalence. Results: 40 cases of HEV were identified. Seven were excluded from study as they contracted HEV outside Cornwall. 132 age/sex match controls were identified. 20/33 HEV cases clustered in the west of Cornwall, indicating that the geographical distribution was not uniform (OR=2.7, 95% CI 1.1 to 6.5, p=0.023). The seroprevalence of anti-HEV IgG in 611 Cornish residents increased gradually with age, and after adjusting for age/sex, there was no difference in seroprevalence between west Cornwall and the remaining study area. There was no difference between cases and controls in distance from the nearest pig farm, socioeconomic status or rainfall during the 8 weeks preceding disease presentation. Cases were more likely to live within 2000 m from the coast (OR=2.78, 95% CI 1.20 to 6.67, p=0.02), and this association remained significant after adjusting for age, sex, urban/rural domicile, proximity to pig farms and socioeconomic status. Conclusion: Cases of HEV are not uniformly distributed in Cornwall and cluster in the west of the county. This is not due to increased exposure to HEV at population level as there was no difference in HEV seroprevalence in the west of Cornwall and the rest of the study area. Proximity to a pig farm does not appear to be a risk factor for contracting HEV. Living within 2000 m of the coast does appear to be a risk factor, but the reason for this is uncertain. Competing interests: None declared. Reference: 1. Ijaz S et al . J Infect Dis 2005;192 :166–72.